Rhetoric of the image of architecture - Grzeszczuk-Brendel, Hanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Based on the example of one of the newsreels of the Polish Film Chronicle of 1965, we have researched the issue of the usability of rhetorical figures for the analysis of the image of architecture recorded in film and its relations with the verbal rhetoric of narration as well as the pictorial rhetoric, which makes up the message of a different nature. By this we have attempted to decode the lifestyle model presented in the film and propagated by its manner of description of architecture with the use of rhetorical figures and also to decode the role and meaning of the architectural forms, which were engaged in the creation of the message of the film image. Combining the rhetorical analysis with an interpretation of the architectural forms has enabled us to identify the persuasive nature of the message of the chronicle material included in the documentary film.